The Construction of Chinese Muslim Identities in Surabaya - Bastian Yunariono; Retno Andriati (Walisongo: Jurnal Penelitian Sosial Keagamaan, 2020)
This study aims to uncover how Chinese Muslims in Surabaya developed their identity in Post-Reformation. During the New Order regime, they could not show their identity as a part of Indonesian diversity. Chinese identity has merged with the “native” people. Along with the downfall of the authoritarian political system and the development of multiculturalism and pluralism, Chinese Muslims in Surabaya could express their cultural identity. This study uses a qualitative method with an ethnographic approach. The results of the study reveal that the Chinese Muslims in Surabaya developed their cultural identity through Cheng Hoo Mosque, Chinese Muslim Organization, and Imlek Celebration. The cultural identity created a hybrid identity which is a combination of Chinese, Java, and Islamic cultures.